2021
DOI: 10.1101/2021.05.01.442239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein secondary structure affects glycan clustering in native mass spectrometry

Abstract: Infection with human noroviruses (hNoV) for the vast majority of strains requires attachment of the viral capsid to histo blood group antigens (HBGA). The HBGA binding pocket is formed by dimers of the protruding domain (P dimers) of the capsid protein VP1. Several studies have focused on HBGA binding to P dimers, reporting binding affinities and stoichiometries. However, nuclear magnetic resonance spectroscopy (NMR) and native mass spectrometry (MS) analyses yielded incongruent dissociation constants (KD) for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…These findings agree with another NMR study but oppose an MS based report . We have recently observed unspecific glycan clustering due to β-sheet rich regions that obstruct native MS-based glycan interaction studies. , This finding may explain the discrepancy, since the RBD contains a twisted five-stranded antiparallel β-sheet …”
supporting
confidence: 88%
See 1 more Smart Citation
“…These findings agree with another NMR study but oppose an MS based report . We have recently observed unspecific glycan clustering due to β-sheet rich regions that obstruct native MS-based glycan interaction studies. , This finding may explain the discrepancy, since the RBD contains a twisted five-stranded antiparallel β-sheet …”
supporting
confidence: 88%
“…19 We have recently observed unspecific glycan clustering due to βsheet rich regions that obstruct native MS-based glycan interaction studies. 32,33 This finding may explain the discrepancy, since the RBD contains a twisted five-stranded antiparallel β-sheet. 27 To further explore the role of sialoglycans as cognate ligands, we subjected 2,3-sialyllactose to STD NMR experiments in the presence of full-length S-glycoprotein, recombinantly produced in HEK cells.…”
mentioning
confidence: 99%
“…11 Years later, it was revealed that the binding and recognition of HBGAs by noroviruses is much more complex than previously anticipated 13 and various studies have demonstrated some hidden traps affecting the interpretation of the binding process a stepwise interaction. 14 Mallagaray et al shed light on HBGAs-norovirus interactions revealing that a spontaneous deamidation of N373, near the HBGA binding site, leads to loss of HBGA recognition and is partly responsible for the misinterpretation of previous binding data as caused by cooperative effects. 15 Our laboratory has reported the recognition of influenza virus hemagglutinin (HA)-containing VLPs for competitive selection from a mixture of α(2,6)-Sialyllactose and α(2,3)-Sialyllactose using STD NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%